Catalytic Decomposition of SO3 over Pt/BaSO4 Materials in Sulfur-Iodine Cycle for Hydrogen Production - Nagaraja, Bhari Mallanna; Jung, Kwang Deog; Ahn, Byoung Sung; Abimanyu, Haznan; Yoo, Kye Sang (AMER CHEMICAL SOC, 2009)
Various platinum-supported barium sulfate catalysts have been employed for SO3 decomposition in sulfur-iodine cycle to produce hydrogen. Before impregnation of platinum, barium sulfate as a support has been prepared by different methods, i.e., using-ethylene glycol (EG) and water by dispersion method and EG and propanol by spray pyrolysis. The influence of the supports on catalytic performance was examined with three catalysts: 1.0Pt/BaSO4 (PrOH), 1.0Pt/BaSO4 (EG), and 1.0Pt/BaSO4 (H2O) at various temperatures for SO3 decomposition. 1.0Pt/BaSO4 (PrOH) prepared by spray pyrolysis showed high SO3 conversion (62%) at low temperature (1023 K) compared with the other catalysts prepared by dispersion method. The effect of Pt loading on catalytic activity has been performed with BaSO4 impregnated by various amounts of platinum. Under identical conditions, the 1.0Pt/BaSO4 Catalyst showed the highest catalytic performance because of high surface area and small particle size of platinum.
Keywords: MESOSTRUCTURED BARIUM-SULFATE; WATER-SPLITTING CYCLE; SPRAY-PYROLYSIS; STABILITY; METHANE; ACID